Vibrational spectroscopic analysis of critical micelle concentration in sodium decanoate solutions - Becherová, Lucia; Prokopec, Vadym; Čejková, Jitka (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
The presented study is devoted to the investigation of the micellization-induced liquid-liquid fluctuations in sodium decanoate (NaD) aqueous solutions, based on the vibrational spectroscopic study of NaD and the determination of critical micelle concentration (CMC) of this system. At the same time, we focused on monitoring the effect of the addition of decanol to this system and changing its basic parameters from the point of view of CMC. CMC is an important parameter from a practical point of view and a characteristic feature of each micelle-forming compound. Upon analyzing the spectroscopic data we focus our attention mainly on the intensity and band position variations of both the symmetrical and antisymmetrical vibrational modes of CH2 groups situated in the high-frequency part of the spectrum. The study used normal (non-enhanced) Raman spectroscopy with excitation wavelength 785 nm, surface-enhanced Raman spectroscopy (SERS) on large-scaled gold-coated SERS-active substrates and infrared spectral measurements. The results of spectroscopic measurements were supported by tensiometry and potentiometry.
Keywords: Vibrational spectroscopy; Critical micelle concentration; Sodium decanoate; Raman spectroscopy